2021
DOI: 10.1111/acer.14614
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of alcohol use disorder severity among nontreatment‐seeking heavy drinkers: An examination of the incentive salience and negative emotionality domains of the alcohol and addiction research domain criteria

Abstract: Background The Alcohol and Addiction Research Domain Criteria (AARDoC) propose that alcohol use disorder is associated with neural dysfunction in three primary domains: incentive salience, negative emotionality, and executive function. Prior studies in heavy drinking samples have examined brain activation changes associated with alcohol and negative affect cues, representing the incentive salience and negative emotionality domains, respectively. Yet studies examining such cue‐induced changes in functional conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…Such deep phenotyping is also in line with multi-method/multi-level transdiagnostic frameworks such as NIMH Research Domain Criteria (Cuthbert, 2022 ). Addictions Neuroclinical Assessment factors (Kwako et al, 2017 ; Nieto et al, 2021 ), and Addiction Research Domain Criteria (Al-Khalil et al, 2021 ). Several past reviews (Houston and Schlienz, 2018 ; Jurado-Barba et al, 2020 ; Zhang et al, 2021b ) summarized SUD-EEG links within these organizing frameworks, linking EEG/ERP metrics to salience (N1, P1, P3/SP, theta); inhibitory control/conflict monitoring/executive (ERN)/NG-N2/P3); and negative emotionality/motivated attention : (LPP, theta, face-elicited P1/N1/N170).…”
Section: Resultsmentioning
confidence: 99%
“…Such deep phenotyping is also in line with multi-method/multi-level transdiagnostic frameworks such as NIMH Research Domain Criteria (Cuthbert, 2022 ). Addictions Neuroclinical Assessment factors (Kwako et al, 2017 ; Nieto et al, 2021 ), and Addiction Research Domain Criteria (Al-Khalil et al, 2021 ). Several past reviews (Houston and Schlienz, 2018 ; Jurado-Barba et al, 2020 ; Zhang et al, 2021b ) summarized SUD-EEG links within these organizing frameworks, linking EEG/ERP metrics to salience (N1, P1, P3/SP, theta); inhibitory control/conflict monitoring/executive (ERN)/NG-N2/P3); and negative emotionality/motivated attention : (LPP, theta, face-elicited P1/N1/N170).…”
Section: Resultsmentioning
confidence: 99%
“…Causal models showed that LDLPFC stimulation had direct influence on within-network RSFC in the IS and NE addiction networks. These results are promising evidence of the modulatory effects of non-invasive neuromodulation on top-down RSFC, specifically from a key executive control cortical region (DLPFC) to key addiction networks involved in reward processing and emotion regulation [5052].…”
Section: Discussionmentioning
confidence: 99%
“…All MRI data were acquired from a 3T Siemens Prisma scanner at the University of Minnesota’s Center for Magnetic Resonance Research (CMRR). Acquisition parameters closely matched those created by the Human Connectome Project (HCP)[4850]. Images collected: a T1-weighted MPRAGE image [TR=2400ms, TE=2.24ms, slices=208, voxel size=0.8mm3], a T2-weighted SPACE image [TR=3200ms, TE=564ms, slices=208, voxel size=0.8mm3], a pair of opposite phase encoded spin echo EPI scans matched to the resting state fMRI, and a resting state fMRI scan [TR=800ms, TE=37ms, slices=72, volumes=520, voxel size=2.0mm3, multiband factor=8, 7 minutes duration].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Some, but not all, prospective and experimental studies have provided support for elevated reward region response to high-calorie food images as a predictor of weight gain [33][34][35][36]. Paralleling these findings, people with substance-use disorders, compared to those without, show greater activation in reward regions of the brain to substance use cues [37,38]. In an activation likelihood estimation meta-analysis of 87 studies, participants with obesity and those with substance addictions exhibited similar blood-oxygen-level-dependent fMRI hyperactivity in the amygdala and striatum when processing general rewarding stimuli as well as problematic stimuli (i.e., food-or drug-related stimuli) [39].…”
Section: Parallels Between Individuals With Obesity or A Sudmentioning
confidence: 91%